النصرانية في الخطاب القرآني :‏ ‏دراسة لآراء الامام الرزى / ‏ - توري, سيكو مارفا أبوبكر (Kulliyah Ma'arif al-Why wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah Maliziya, 2010)
This research has made an attempt to study Christianity in the Qur'anic discourse: faith, ethics, and founder, while identifying the Qur'anic position in relation to these issues. The study has been done in light of al-Razi's thought, clarifications and explanations of the Qur'anic texts, with special reference to Mafatih al-Ghayb, Munazarah fl al-Radd 'ala al-Nasara and I'tiqadat firaq al-Muslimin wa al-Mushrikin. The researcher has also made an attempt to discuss the important issues considered as fundamentals in Christianity, such as the doctrine of paternity, divinity of Jesus, divinity of Mary, trinity, redemption and doctrine of crucifixion of Jesus. Furthermore, this study has been done on other major issues which have close relation to Christianity as a religion dealt by the holy Qur'an; these issues include names and titles of Jesus in the Qur'an, the annunciation, the birth and death of Jesus, his teachings, his miracles, and the Gospel. It is important to remember that the research has dealt with some great figures concerned by Christians, like Zachariah, his son John the Baptist, the apostles and Mary. The research has also identified the arguments used to undermine the authenticity of the Quranic version of events and subjected these arguments to proper scrutiny. In addition, the researcher has made an attempt to point out both Qur'anic methodology and al-Razi's method in dealing with Christianity.